KELAS IBU HAMIL UNTUK MEWUJUDKAN “ISIS GAYA” (IBU SEHAT BAYI SELAMAT KELUARGA BAHAGIA) - Nina Zuhana; Suparni Suparni; Wahyu Ersila (Universitas Muhammadiyah Semarang, 2017)
Maternal Classroom Activity is a tool for group learning about health for pregnant women, in the form of face-to-face that aims to improve knowledge and skills of pregnant women about pregnancy, childbirth, postpartum care and newborn care, through practice by using KIA book (Maternal Child Health ) The aims of this Ibm is the increasing knowledge of pregnant women about postpartum pregnancy care, newborn care, pregnant mother's readiness for exclusive breastfeeding, Increased maternal health during pregnancy with pregnancy exercises, pregnant women's preparation to face labor with breathing exercises, Knowledge of health status Pregnant women with the examination of pregnant women support includes blood pressureexamination, Hb. Ibm is done in the village of Ambukembang which is the work area of Kedungwuni II health center for 6 months starting from March until August 2017. The results of this Ibm activity is 90% of pregnant women enthusiastic about the activities undertaken. Conducive activity, comfortable place forpregnant women. And 93.3% of pregnant women who participated in this activity are active and interested inmaternity health matter and activity checks. For health workers especially midwives more motivate pregnant women to always follow the classroom activities of pregnant women. And required cooperation from the village government and health offices related to the pregnancy class pregnancy order activities can runeffectively.Keywords: class of pregnant women, ISIS STYLE